2020
DOI: 10.31234/osf.io/w7pr6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring socio-emotional skills in schools: simple questionnaires outperform behavioral tasks

Abstract: Recent empirical research has shown that improving non-cognitive skills such as grit, conscientiousness and self-control leads to higher academic achievement and better life outcomes. These findings have motivated the creation of educational programs targeting non-cognitive skills around the world. However, both theoretical and empirical works have raised concerns about the reliability of the different methods used to measure non-cognitive skills. The purpose of this study is to compare three methods of measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Note that the initial student survey also included the Academic Diligence Task developed by Galla et al, 2014 as a behavioral measure of diligence. Our prior was that a behavioral task would do better than questionnaires to measure diligence, but it turned out that it was no more reliable, and less valid, than self-reported and teacher-reported measures of diligence, a result that we show in a companion paper (Boon-Falleur et al, 2020). Given that the task is a costly instrument both financially and logistically, we removed it from the survey in the last two years and do not use it in this paper.…”
Section: Data Sources and Descriptionmentioning
confidence: 99%
“…Note that the initial student survey also included the Academic Diligence Task developed by Galla et al, 2014 as a behavioral measure of diligence. Our prior was that a behavioral task would do better than questionnaires to measure diligence, but it turned out that it was no more reliable, and less valid, than self-reported and teacher-reported measures of diligence, a result that we show in a companion paper (Boon-Falleur et al, 2020). Given that the task is a costly instrument both financially and logistically, we removed it from the survey in the last two years and do not use it in this paper.…”
Section: Data Sources and Descriptionmentioning
confidence: 99%
“…This constrains the applicability of CAID for clinical assessment and research. A particular concern is the degree to which inferences can be made about people or dyads, in general, from data that were collected in one specific situation (e.g., Boon-Falleur et al, 2020;Hedge et al, 2018;Woods & Wright, 2019). In this study, we use Generalizability Theory (Cronbach et al, 1963) analyses to decompose the sources of variance in CAID ratings.…”
Section: Continuous Assessment Of Interpersonal Dynamicsmentioning
confidence: 99%
“…Such a discrepancy between economic games and questionnaires is not an isolated finding and raises interesting questions about the validity of economic games to study realworld cooperation (Becker et al, 2012;Boon-Falleur et al, 2020;Chuang & Schechter, 2015;Dang et al, 2020;Lönnqvist et al, 2015). For instance, a recent systematic review and metaanalysis (Galizzi & Navarro-Martinez, 2019) found only weak evidence of a correlation (r = 0.14) between economic games and social behaviour in the field.…”
Section: Discussionmentioning
confidence: 99%